2014
DOI: 10.1108/itp-04-2012-0041
|View full text |Cite
|
Sign up to set email alerts
|

A collective artefact design of decision support systems: design science research perspective

Abstract: Purpose -The knowledge of artefact design in design science research can have an important application in the improvement of decision support systems (DSS) development research. Recent DSS literature has identified a significant need to develop user-centric DSS method for greater relevance with respect to context of use. To address this, this study develops a collective DSS design artefact as method in a practical industry context. Design/methodology/approach -Under the influence of goal-directed interaction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…As for the quantitative data, statistical analysis will be used to determine the similarity or difference between years, to isolate causes and effects, and to eliminate outliers. At the interpretation phase, the collected qualitative data will be transformed into the quantitative data and compared with the quantitative data to establish criteria that will be used to build rules and algorithms for framework that will be implemented in expert systems using design science method (Miah et al 2014(Miah et al , 2009). …”
Section: Phenomena Study and Analysismentioning
confidence: 99%
“…As for the quantitative data, statistical analysis will be used to determine the similarity or difference between years, to isolate causes and effects, and to eliminate outliers. At the interpretation phase, the collected qualitative data will be transformed into the quantitative data and compared with the quantitative data to establish criteria that will be used to build rules and algorithms for framework that will be implemented in expert systems using design science method (Miah et al 2014(Miah et al , 2009). …”
Section: Phenomena Study and Analysismentioning
confidence: 99%
“…Fisher & Craig 2005) and decision support systems (DSS) for farmers (e.g. Breuer et al 2009;Cabrera et al 2008;Huang et al 2010;Jakku & Thorburn 2010;Miah et al 2014). We also review studies in developing countries, including Kenya (Gichamba & Lukandu 2012;Oduor et al 2018), Ethiopia (Zewge et al 2014;, Tanzania (Churi et al 2013), South Africa (Doerflinger & Dearden 2013;Merz et al 2007), Tunisia (Ndou et al 2011), Malaysia (Noor & Nordin 2012), and Bangladesh (Islam & Grönlund 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Governments and other types of organisations develop information systems (IS) to support SMEs. For example, governments may develop decision support systems (DSS) to help farmers optimise land use (Miah et al 2014), or develop websites which save SMEs time to access services and achieve compliance (Holgersson 2014). Organisations develop DSS for use by SMEs, including farmers, in developing countries in Africa (Doerflinger & Dearden 2013;Oduor et al 2018) and South East Asia (Noor & Nordin 2012).…”
Section: Introductionmentioning
confidence: 99%
“…DSS development research has indicated the need to develop and employ more-rigorous methods for DSS solution development (Arnott & Pervan, 2005, 2008Miah, Kerr and von Helens, 2014;Miah and Gammack, 2014). This need can be addressed through a substantial exploration and improvement in design research.…”
Section: Study Backgroundmentioning
confidence: 99%